(untitled) (PANGEEA, 2025)
Knowing the maximum flow rates, as well as the maximum volumes of the floods with different probabilities is necessary in dimensioning and exploitation of hydrotehnical constructions, the safety and efficiency of the works depending greatly on the data accuracy. In the case where measurement data exists in cross-sections location of works, we rely on bidimensional probabilities or correlations between hydrological units. With that in mind, the methodology and a computation example highlighting the two hydrological elements (maximum flow rate and maximum volume) of floods for the desired probabilities are presented in the paper.